# 2sinx*cosx-sinx-cosx-1=0

## Simple and best practice solution for 2sinx*cosx-sinx-cosx-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for 2sinx*cosx-sinx-cosx-1=0 equation:

Simplifying
2sinx * cosx + -1sinx + -1cosx + -1 = 0
Multiply insx * cosx
2cinos2x2 + -1sinx + -1cosx + -1 = 0
Reorder the terms:
-1 + 2cinos2x2 + -1cosx + -1insx = 0
Solving
-1 + 2cinos2x2 + -1cosx + -1insx = 0
Solving for variable 'c'.
Move all terms containing c to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 2cinos2x2 + -1cosx + 1 + -1insx = 0 + 1
Reorder the terms:
-1 + 1 + 2cinos2x2 + -1cosx + -1insx = 0 + 1
Combine like terms: -1 + 1 = 0
0 + 2cinos2x2 + -1cosx + -1insx = 0 + 1
2cinos2x2 + -1cosx + -1insx = 0 + 1
Combine like terms: 0 + 1 = 1
2cinos2x2 + -1cosx + -1insx = 1
Add 'insx' to each side of the equation.
2cinos2x2 + -1cosx + -1insx + insx = 1 + insx
Combine like terms: -1insx + insx = 0
2cinos2x2 + -1cosx + 0 = 1 + insx
2cinos2x2 + -1cosx = 1 + insx
Reorder the terms:
-1 + 2cinos2x2 + -1cosx + -1insx = 1 + insx + -1 + -1insx
Reorder the terms:
-1 + 2cinos2x2 + -1cosx + -1insx = 1 + -1 + insx + -1insx
Combine like terms: 1 + -1 = 0
-1 + 2cinos2x2 + -1cosx + -1insx = 0 + insx + -1insx
-1 + 2cinos2x2 + -1cosx + -1insx = insx + -1insx
Combine like terms: insx + -1insx = 0
-1 + 2cinos2x2 + -1cosx + -1insx = 0
The solution to this equation could not be determined.`